Keynesian and post-Keynesian models on banks in Africa - Tche, Jacob (Brazilian Keynesian Review, 2024)
In the present paper, we aim at filling the lacuna created by the lack of a multiplicity of empirical works on Keynesian and Post-Keynesian models on banks in Africa. Based on the case of banks and economic growth in 20 Sub-Sahara African countries for the 1990-2021periods, we employ the Granger causality tests in heterogeneous panels developed by Dumitrescu and Hurlin (2012), the Fixed Effect Ordinary Least Squares method, the Mean Group Method and the Generalized Method of Moments to conclude that, in the short and long run, economic growth precedes banks development  as justified by Keynesian and Post-Keynesian bank models.